A METHOD FOR PREDICTING THE SPREAD OF EPIDEMIOLOGICAL THREATS BASED ON THE TELEGRAPH EQUATION - Маланчук, Оксана (SWorldJournal, 2025)
Mathematical modeling of epidemic dynamics plays a crucial role in understanding, predicting, and controlling the spread of infectious diseases. Traditional approaches are often based on diffusion-type equations, which assume instantaneous propagation of